2017
DOI: 10.1128/mbio.00097-17
|View full text |Cite
|
Sign up to set email alerts
|

The Proximity of Ribosomal Protein Genes to oriC Enhances Vibrio cholerae Fitness in the Absence of Multifork Replication

Abstract: Recent works suggest that bacterial gene order links chromosome structure to cell homeostasis. Comparative genomics showed that, in fast-growing bacteria, ribosomal protein genes (RP) locate near the replication origin (oriC). We recently showed that Vibrio cholerae employs this positional bias as a growth optimization strategy: under fast-growth conditions, multifork replication increases RP dosage and expression. However, RP location may provide advantages in a dosage-independent manner: for example, the phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 58 publications
6
45
0
Order By: Relevance
“…Even though rRNA operons in S. pneumoniae are also initiated with GTP (BioRxiv: https://doi.org/10.1101/283663), we did not observe a correlation between initiating nucleotide and gene expression levels in cells growing in different media (Supplementary Figure S2C). Nevertheless, in prokaryotes including S. pneumoniae, genes encoding ribosomal RNAs and proteins are conserved in a location close to the origin of replication (50)(51)(52). The ori-proximal location of the four pneumococcal rRNA loci results in a higher gene copy number of rRNAs in fast-growing cells, such as in C+Y, as a direct consequence of the increase in replication initiation frequency.…”
Section: Dmentioning
confidence: 99%
“…Even though rRNA operons in S. pneumoniae are also initiated with GTP (BioRxiv: https://doi.org/10.1101/283663), we did not observe a correlation between initiating nucleotide and gene expression levels in cells growing in different media (Supplementary Figure S2C). Nevertheless, in prokaryotes including S. pneumoniae, genes encoding ribosomal RNAs and proteins are conserved in a location close to the origin of replication (50)(51)(52). The ori-proximal location of the four pneumococcal rRNA loci results in a higher gene copy number of rRNAs in fast-growing cells, such as in C+Y, as a direct consequence of the increase in replication initiation frequency.…”
Section: Dmentioning
confidence: 99%
“…In line with prior bioinformatics studies (16, 17), we showed that oriC -proximity of S10 provides optimal dosage and expression to attain the maximal growth capacity (19). We also found that S10 position impacts bacterial fitness in absence of multi-fork replication (20). This suggests that the RP gene location affects cell physiology even in slow-growing bacteria (20).…”
Section: Introductionmentioning
confidence: 79%
“…In previous works (19, 20), we tackled this issue in Vibrio cholerae , the causative agent of cholera disease. This microorganism is also a model for multi-chromosomal bacteria, a trait found in ~10% of these microorganisms (21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the increase in gene dosage due to bacterial multifork replication appears as an added control mechanism of natural genetic circuits (37,38). However, the relevance of genome organization goes beyond gene dosage fluctuations in fast growth (39,40), and it may be influenced by chromosomal structure (39) and gene essentiality (41).…”
Section: Discussionmentioning
confidence: 99%